Fry production, induced breeding practices and cost-profit analysis of the hatcheries of Rajshahi district in Bangladesh - Aktar, Naima; Bhuiyan, Abdus Salam; Islam, M Nazrul (Journal of Fisheries, 2014)
This study was conducted on the 13 hatcheries of Rajshahi district from March to December 2013 to know about the fry production status, induced breeding practices and cost-profit status. Average fry production of Labeo rohita, 93.38±83.32 kg, Catla catla, 62.00±60.84 kg, Cirrhinus cirrhosus, 77.46±58.61 kg, L. calbasu, 14.20±14.60 kg, L. bata, 53.73±50.56 kg, L. gonia, 10.00±0 kg, Heteropneustes fossilis, 5.00±0 kg, Clarias batrachus, 20.00±0 kg, Hypophthalmichthys molitrix, 149.77±138.45 kg, Aristichthys nobilis, 104.54±148.11 kg, Ctenopharyngodon idella, 19.20±15.35 kg, Cyprinus carpio 108.08±77.39 kg and Barbonymus gonionotus, 23.10±14.04 kg were recorded in the surveyed hatcheries. Two types of hormone injections PG (pituitary gland) and HCG (Human chorionic gonadotropin) were used for induced breeding. The rate of 1st dose of injection of PG varied from 1 to 2 mg/kg and HCG from 100-150 IU/kg and the rate of 2nd dose of injection of PG varied between 5 and 8 mg/kg. The incubation period and hatching rate in different fish species varied from 10 to 72 hours and 55% to 80%, respectively. The average total cost, gross return and net profit of the hatcheries were 0.667±0.798, 1.152±1.636 and 0.485±0.846 million BDT respectively.